1988
DOI: 10.1016/0014-5793(88)80596-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myosin heavy chain stoichiometry in pig tracheal smooth muscle during development

Abstract: The stoichiometry of the myosin heavy chains (MHCs) has been measured in the tracheal smooth muscle of the pig after electrophoresis on SDS 4% polyacrylamide gel. The ratio of slower migrating MHC to the faster migrating MHC was 2.1 neonates, 1.5 in young and 0.95 in old pigs (P less than 0.01) showing that MHC composition changes with development. The unequal proportion of MHCs was not compatible with a heterodimeric arrangement of the MHCs in the native molecule as proposed earlier by Rovner et al. [(1986) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…SM 2 accounted for the majority, if not all, of the 200-kD isoform and was present throughout development, expression increasing~2-fold, whereas SM 1 decreased. Similar alterations have been seen in tracheal smooth muscle from neonatal and large adult pigs (30). In contrast, at~120-d gestation the ovine fetal aorta expressed smaller amounts of SM 1 than the 200-kD MHC isoform, which appears to be predominantly MHC-B.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…SM 2 accounted for the majority, if not all, of the 200-kD isoform and was present throughout development, expression increasing~2-fold, whereas SM 1 decreased. Similar alterations have been seen in tracheal smooth muscle from neonatal and large adult pigs (30). In contrast, at~120-d gestation the ovine fetal aorta expressed smaller amounts of SM 1 than the 200-kD MHC isoform, which appears to be predominantly MHC-B.…”
Section: Discussionsupporting
confidence: 66%
“…Although nonmuscle MHC isoforms have been observed in aortic smooth muscle from adult animals and humans (9,12,14), they are not present in adult bovine (15) or rabbit (16) aorta or adult ovine uterine artery, myometrium or bladder (22), which may reflect species differences. During development SM 1 is expressed to varying but significant extent in several smooth muscle tissues from the fetus and neonate (3,5,9,12,(14)(15)(16)30), whereas the composition of the remaining MHC is variable. However, it has become more evident that the predominant lower molecular weight species expressed in fetal and neonatal aorta are the nonmuscle MHC isoforms, which only can be identified using Western analysis because of their similar electrophoretic mobilities (9,12,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In the rodent ventricle, the slow migrating MHC isoform is predominant in fetal life, whereas the faster migrating MHC is more prevalent during adult life (21). In the pig tracheal smooth muscle, there is a decrease in the ratio of MHCl to MHC2 during maturation (24), whereas similar work on human tracheal smooth muscle failed to show any change in MHC isoform with maturation (25).…”
Section: Newborn Fundusmentioning
confidence: 80%
“…In studies using swine trachealis muscle, myosin content either increased from fetus to adult (23) or decreased from 2 to 10 wk postnatal age (24). Investigators have shown differences in myosin isoforms between embryonic, neonatal, and adult smooth muscle in both airway (23)(24)(25) and nonairway smooth muscle (26,27). Although any or all of these mechanisms may be responsible for the observed increase in force generation with age, the present study did not attempt to identify the causes of increased contractility.…”
Section: Newbornmentioning
confidence: 99%